Factors That Affect Frim Value In Mining Sector Companies Listed On The Indonesia Stock Exchange For The Period 2020-2023 - NURHIDAYAH, SOFIATUN; Rita Meiriyanti; Prianka Ratri Nastiti (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
This research aims to empirically prove the influence of profitability, leverage and company size on company value in mining companies listed on the Indonesia Stock Exchange for the 2020-2023 period. The data used in this research is secondary data in the form of annual reports of mining companies listed on the Indonesia Stock Exchange for the 2020-2023 period. The sampling method used purposive sampling, so that 24 samples were obtained from 83 companies. This research uses multiple linear regression analysis. Before carrying out regression analysis, the classical assumptions are first tested. The results of this research partially show that the variables profitability, leverage and company size influence company value.